Peningkatan Kualitas Visual dan Ketahanan Ekonomi melalui Pemanfaatan Barang Bekas dengan Vertical Garden Hidroponik - Utami, Tin Budi; Susetyo, Budi; Pratiwi, Riri (Jurnal Abdi Masyarakat (JAM), 2025)
Kelurahan Meruya Selatan area in West Jakarta's high-density population, in each resident's house has a rare Green Open Space (RTH). Meruya Selatan Village area, namely 2.8 km². So that the visual quality decreases due to uncontrolled development and limited land. With the densely populated condition of the Meruya Selatan Village and polluted air, reforestation is very much needed. There are many ways to reforest, including a hydroponic vertical garden. The advantage of vertical hydroponic planting is the efficiency of land use. Cultivating plants using this technique is very profitable for those who do it. Such as harvesting plants can be faster, healthier, with maximum results, and can utilize plastic waste by converting used bottles into hydroponic planting media. And can make this environment beautiful and comfortable. Utilization of yard land is one way to increase household-scale food security. Thus, it is hoped that every community participating in hydroponics will help their economic system